A new geometry for improving the strength of single lap joints using adherend notching technique. Issue 11 (18th August 2021) - Beigrezaee, M.J.; Ayatollahi, M. R.; Bahrami, B.; da Silva, L.F.M.
ABSTRACT: In this study, the adherend notching technique is reconsidered by introducing a rectangular or a semi-circular notch on the outer surface of the adherends in the single lap joint (SLJ). Firstly, an extensive finite element (FE) analysis was conducted to numerically investigate the effect of different notch parameters on the strength enhancement of the SLJs. Improvement of the peak of peel stress along the overlap length was selected as the determinative factor for obtaining the optimum parameters of the introduced notch. Then, a set of experiments were performed on the notched SLJs based on the optimum notch parameters derived in the FE analyses and the experimental failure loads were compared with the un-notched SLJs. The experimental results showed that introducing a notch can improve the strength of SLJs up to 110% which demonstrates the effectiveness of the proposed technique in this paper. Furthermore, it was seen that there is not a meaningful difference between the improvements of rectangular and semi-circular notch which shows that the improvement of the adherend notching technique are not dependent on the geometry of the introduced notch.